An Evaluation of the Need for Selected Trade Facilitation Measures in Indonesia: Implications for the WTO Negotiations on Trade Facilitation - Yose Rizal Damuri (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
As a member of WTO, Indonesia has been involved in the discussion of the WTO negotiating group on trade facilitation (NGTF). This study aims to examine the current situation of trade facilitation in Indonesia, as well to assess the needs and priorities of various measures related to the trade facilitation negotiations.
Keywords: F1; 330; WTO; Trade Facilitation; Indonesia